The Impact of Liver Transplantation after Surgical Treatment of Hepatocellular Carcinoma - Topal, Halit; Tiek, Joyce; Fieuws, Steffen; Pirenne, Jacques; Nevens, Frederik; Topal, Baki (Frontiers in Surgery, 2014)
Background The impact of liver transplantation (LTx) after surgical treatment for HCC remains undefined. The aim of the current study was to assess the impact of LTx and of selection criteria for LTx on the survival of patients who underwent surgery for HCC. Methods Between 2004 and 2009, 119 patients underwent surgical treatment for HCC. Cirrhosis was present in 85 patients. Of all patients, 77 fulfilled the Milan criteria, 88 the UCSF and 87 the Up-to-7 criteria. Finally, 35 patients received an LTx, of whom 31 met the Milan, 33 the UCSF, and 33 the Up-to-7 criteria. The relation between LTx and survival was evaluated using a Cox regression model with LTx as a time-dependent factor. Results Median (95% confidence interval (CI)) disease-free (DFS) and overall survival (OS) of the entire patient population was 9.4 (7 - 12.2) and 49.1 (37.7 - 64) months, respectively. The 1, 3, and 5-year DFS vs. OS rates were 36%, 3%, and 0% vs. 84.7%, 61.7%, and 39.6%, respectively. Patients fulfilling the Milan criteria had a significantly better OS and DFS than those who had tumors beyond the Milan criteria (p < 0.047). No significant differences were observed in terms of OS between patients within vs. beyond the UCSF or Up-to-7 criteria (p > 0.130). In multivariable analysis, cirrhotic patients who received an LTx had a better OS, with a HR equal to 0.25 (95% CI: 0.08-0.74; p<0.01). LTx after surgery had a beneficial impact on both DFS and OS of patients in all the 3 selection criteria models of LTx (p<0.031). Conclusion Liver transplantation after primary surgery seems to offer the best long-term survival for patients suffering from HCC in cirrhosis as well as for them who fulfill the Milan, UCSF, and Up-to-7 criteria.